Biological Activities of the Whole Grass Extracts from Amaranthus viridis L. - Jin, Ying-Shan; Jin, Yinzhe; Li, Chunmei; Chen, Manli; Jin, Yunzhe; Piao, Jiyu; Xuan, Yonghao (Asian Journal of Chemistry, 2013)
Amaranthus viridis L. is a traditional medicine in Asia. In this study, the antioxidant activities of petroleum ether, ethyl ether, ethyl acetate, n-butanol and water extracts of A. viridis L. were evaluated with various antioxidant assays, including DPPH (1,1-diphenyl-2-pricrylhydrazyl) free radical scavenging, xanthine oxidase inhibitory, hydroxyl radical scavenging, lipid peroxidation scavenging and protein damage assay. All the extracts had strong antioxidant activity in the DPPH scavenging, lipid peroxidation scavenging and xanthine oxidase inhibitory. The petroleum ether extract had the highest hydroxyl radical scavenging activity. Its activity was equivalent to quercetin at 0.25 mg/mL. Inhibition effect on a-glucosidase of 0.5 mg/mL extract was also evaluated and the petroleum ether fraction had the highest inhibitory activity. Its activity was slightly lower than that of acarbose at 0.5 mg/mL, indicating that A. viridis L. extracts may have antidiabetic activity. Antimicrobial activity (10 mg/mL extract) was also evaluated and the ethyl ether extract had the highest antimicrobial activity. Its activity was slightly lower than that of cefalexin, indicating that A. viridis L. extracts may have antimicrobial activity. These results suggest that A. viridis L. may have health-enhancing effects.